Potential for Ammonia Recapture by Farm Woodlands: Design and Application of a New Experimental Facility - Mark R. Theobald; Mark C. Milford; Mark K.J. Hargreaves; Mark L.J. Sheppard; Mark E. Nemitz; Mark Y.S. Tang; Mark V. R. Phillips; Mark R. Sneath; Mark L. McCartney; Mark F. J. Harvey; Mark I. D. Leith; Mark J. N. Cape; et al. (The Scientific World Journal)
There has been increasing pressure on farmers in Europe to reduce the emissions of ammonia from their land. Due to the current financial climate in which farmers have to operate, it is important to identify ammonia control measures that can be adopted with minimum cost. The planting of trees around farmland and buildings has been identified as a potentially effective and low-cost measure to enhance ammonia recapture at a farm level and reduce long-range atmospheric transport. This work assesses experimentally what fraction of ammonia farm woodlands could potentially remove from the atmosphere. We constructed an experimental facility in southern Scotland to simulate a woodland shelterbelt planted in proximity to a small poultry unit. By measuring horizontal and vertical ammonia concentration profiles within the woodland, and comparing this to the concentration of an inert tracer (SF6) we estimate the depletion of ammonia due to dry deposition to the woodland canopy. Together with measurements of mean ammonia concentrations and throughfall fluxes of nitrogen, this information is used to provide a first estimate of the fraction of emitted ammonia that is recaptured by the woodland canopy. Analysis of these data give a lower limit of recapture of emitted ammonia, at the experimental facility, of 3%. By careful design of shelterbelt woodlands this figure could be significantly higher.